PENGARUH BUSINESS RELATIONSHIP FUNCTION TERHADAP RELATIONSHIP QUALITY DAN BUYER PERFORMANCE DI CV. CAHAYA ABADI DI SURABAYA - Muhammad Alif Alfiansyah (CALYPTRA, 2019)
Abstrak - Penelitian ini bertujuan untuk mengetahui dan menguji pengaruh business relationship function, terhadap relationship quality dan buyer performance di CV. Cahaya Abadi di Surabaya. Pengolahan data dilakukan dengan menggunakan software SPSS AMOS 13. Teknik pengambilan sampel yang digunakan adalah probability sampling. Jumlah sampel yang digunakan dalam penelitian ini adalah sebanyak 125 responden yang memenuhi karakteristik populasi yag telah ditentukan dan diperoleh dari penyebaran kuesioner secara offline. Hasil penelitian ini menunjukan adanya pengaruh positif business relationship function terhadap buyer performance, pengaruh positif business relationship function terhadap relationship quality, pengaruh positif relationship quality terhadap buyer performance serta availability of alternative supplier memudahkan hubungan antara business relationship function dan relationship quality. Kata kunci: Business Relationship Function, Relationship Quality, Buyer's Performance, Availability of Alternative Supplier. Abstract - The purpose of this research is to understand and analyze the influence of business relationship function toward relationship quality and buyer perforrmance in CV. Cahaya Abadi in Surabaya. Data processing was conducted using software SPSS Amos 13. The sampling technique that used is probability sampling. 125 respondents who qualify the specified characteristics of the population were the total of sample used in this research which distributed by offline quetionaire. The result of the research shows the positive relationship of business relationship function to buyer performance, positive relationship of business relationship to relationship quality, positive relationship relationship to buyer performance and availability of alternative supplier such as relationship between business relation function and relationship quality. Keywords: Business Relationship Function, Relationship Quality, Buyer's Performance, Availability of Alternative Supplier